Microbial community structure in air of strong-flavor Baijiu brewing area - WANG Xiuxiu, WANG Junqing, LV Zhiyuan, LIU Yutao, ZHANG Mengmeng, SHANG Hailin, REN Guanghua, ZHANG Chenxi, ZHANG Chengzhen (Zhongguo niangzao)
In order to investigate the microbial community structure in air of different regions of strong-flavor (Nongxiangxing) Baijiu distillery, the microbial community structure and distribution in air of Baotuquan strong-flavor distillery, outside and inside the brewing workshop were studied by Illumina Miseq high-throughput sequencing technology. The results showed that the microbial community in the air samples of distillery was the richest and the highest in diversity, while the diversity in the brewing workshop was low, indicating that in the long-term brewing process, the microorganisms that were not suitable for the brewing environment were eliminated after continuous screening, and a relatively stable microbial flora suitable for the environment was formed by the appropriate microbial enrichment. A total of 748 bacterial operational taxonomic units (OTUs) and 340 fungal OTUs were detected in all the air samples. A total of 20 bacterial phyla and 289 bacterial genera and 7 fungal phyla and 149 fungal genera were noted. The bacterial community in the air samples of different distillery areas was different, while the similarity of the fungal community was high. Compared with the microorganism in air samples of distillery, the microbial communities inside and outside the brewing workshop were more similar. In addition, the unique microbial communities such as Paracococcus were found in the brewing workshop of strong-flavor Baijiu brewed by mechanization.